2019
DOI: 10.1186/s12951-018-0436-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparative mouse lung injury by nickel nanoparticles with differential surface modification

Abstract: BackgroundPrevious studies have demonstrated that exposure to nickel nanoparticles (Nano-Ni) causes oxidative stress and severe, persistent lung inflammation, which are strongly associated with pulmonary toxicity. However, few studies have investigated whether surface modification of Nano-Ni could alter Nano-Ni-induced lung injury, inflammation, and fibrosis in vivo. Here, we propose that alteration of physicochemical properties of Nano-Ni through modification of Nano-Ni surface may change Nano-Ni-induced lung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
63
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 68 publications
3
63
1
3
Order By: Relevance
“…The induction of GIT lesions by HPB seems to correlate with our recent study where we reported the presence of significantly high levels of Cr above MRL limit in this herbal preparation [20]. Similar morphological changes were observed in the lungs of rats that received HPC with the alveolar showing inflammatory changes dominated by lymphocytes and macrophages and alveolar spaces obscured by debris and chronic inflammatory cells which could be attributed to the heavy metal contaminations previously identified at concentrations above their respective MRL values [20,37].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The induction of GIT lesions by HPB seems to correlate with our recent study where we reported the presence of significantly high levels of Cr above MRL limit in this herbal preparation [20]. Similar morphological changes were observed in the lungs of rats that received HPC with the alveolar showing inflammatory changes dominated by lymphocytes and macrophages and alveolar spaces obscured by debris and chronic inflammatory cells which could be attributed to the heavy metal contaminations previously identified at concentrations above their respective MRL values [20,37].…”
Section: Discussionsupporting
confidence: 86%
“…In addition, the relative weight of the lungs of HPB(10) group was significantly higher than that of the control group. In our recent study, we identified HPs (A, B and C) to have been contaminated with nickel, lead and chromium (residual contents greater than maximum residual limit (MRL) values) [29], and previous studies have also linked Ni overexposure to lung injury, inflammation, fibrosis and cancer of the respiratory tract [37]. Considering the dose-related inflammatory changes in the rat lungs and other signs of pulmonary toxicity, it is possible, therefore, that exposure to the Ni content of the HPs may contribute to the observed lung toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…MMPs cleave components of the extracellular matrix as well as other substrates, including cytokines and cell surface adhesion receptors [31]. Previous studies have shown increased expression of MMPs in bronchoalveolar lavage following exposure of mice to Ni NPs [32], in human monocytes exposed to Ni NPs [33] as well as in the nasal lavage fluid of welders exposed to nickel-containing welding particles [34]. The two latter studies also found increased expression of TIMP-1.…”
Section: Discussionmentioning
confidence: 93%
“…Nanoparticles (NPs) are materials or structures with a dimension at 1-100 nm range (Nakamura and Watano 2018). Metal NPs are widely used in industry such as chemical catalysts, ceramic capacitors, sensors, hydrogen storage, conductive pains and biological nanomedical applications due to their physicochemical characteristics (Mo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%